Modelling the three-dimensional vibration of composite archery arrows under free-free boundary conditions - Rieckmann, M.; Park, J. L.; Codrington, J.; Cazzolato, B. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2012)
Archery performance has been shown to be dependent on the resonance frequencies and operational deflection shape of the arrows. This vibrational behaviour is influenced by the design and material of the arrow and the presence of damage in the arrow structure. In recent years arrow design has progressed to use lightweight and stiff composite materials. This paper investigates the vibration of composite archery arrows through a finite difference model based on Euler-Bernoulli theory, and a three-dimensional finite element modal analysis. Results from the numerical simulations are compared to experimental measurements using a Polytec scanning laser Doppler vibrometer (PSV-400). The experiments use an acoustically coupled vibration actuator to excite the composite arrow with free-free boundary conditions. Evaluation of the vibrational behaviour shows good agreement between the theoretical models and the experiments.